INOVASI PEMBIAYAAN HIJAU (GREEN FINANCING) BAGI WIRAUSAHA MUDA: ANALISIS AKSESIBILITAS DAN DAMPAKNYA TERHADAP PERTUMBUHAN - Eriklex Donald; Lutfi Alhazami; Muhamad Al Faruq Abdullah; Dwi Sapto Febriantaka; Izmirta Rachman (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
Green financing is increasingly promoted to accelerate the green transition, yet young entrepreneurs often face barriers in accessing green-oriented capital. This study examines (1) how green financing accessibility influences the adoption of green financing innovations and (2) how both accessibility and adoption affect young venture growth. Using a survey of 250 Indonesian young entrepreneurs (18–35 years old) and partial least squares structural equation modeling (PLS-SEM), the findings show that accessibility significantly increases adoption of green financing innovations (β = 0.52, p < 0.001). Adoption, in turn, positively affects venture growth (β = 0.41, p < 0.001), while accessibility also has a smaller but significant direct effect on growth (β = 0.21, p = 0.004), indicating partial mediation. Credibility signals (e.g., transparent disclosure, third-party verification, and reputable early backers) strengthen the effect of accessibility on adoption (β = 0.15, p = 0.031). The model explains 27% of variance in adoption and 43% of variance in growth. The novelty lies in operationalizing “green financing accessibility” as a multi-dimensional construct tailored to young entrepreneurs and testing its impact pathway to growth through innovation adoption.